PENERAPAN EOQ PROBABILISTIK SEDERHANA DALAM PENGENDALIAN PERSEDIAAN SUKU CADANG DI GUDANG AUTO2000 CABANG BANDUNG SUCI - Fatayatul Fithriyah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Auto2000 Bandung Suci is one of the official dealers selling Toyota products in the city of Bandung. One of the main activities that is very influential in the smooth running of the company's business processes is inventory control of the stock of goods in the warehouse. At Auto2000 Bandung Suci, the most prominent problem in the warehouse is the problem of inventory control that is less than optimal, causing overstock. This study uses a Simple Probabilistic Model which aims to control inventory by knowing the optimum order quantity, reorder point, safety stock, order frequency in a year and total inventory cost. This research resulted in a new policy that can be implemented in the company, namely for the DCS Super Engine Conditioner Product which has an optimum number of orders of 123 units with a total of IDR 240,007,102. The OIG Catalytic System Clean product has an optimum number of orders of 101 units with a total of IDR 137,591,933. Castrol Magnetec Stop-Start products have an optimal order quantity of 103 units, totaling IDR 84,495,104. The Ekatronic Brake Cleaner product has an optimum number of orders of 292 units with a total of IDR 82,340,379. The Kenjiro 250ml Fuel System Cleaner product has an optimum number of orders of 68 units with a total of IDR 68,100,414. The Chamber Clean Diesel product has an optimum number of orders of 59 units with a total of IDR 29,165,522. The Castrol Magnetec 5W-30 product has an optimal order quantity of 64 units, safety stock of 8 units with a total of IDR 62,062,392. The Oil Optimizer Myber Up product has an optimal number of orders of 88 units with a total of IDR 45,098,513.